Fabrication and characterization of chitosan/OGP coated porous poly(ε-caprolactone) scaffold for bone tissue engineering. Issue 9 (13th June 2017) - Cui, Zhixiang; Lin, Luyin; Si, Junhui; Luo, Yufei; Wang, Qianting; Lin, Yongnan; Wang, Xiaofeng; Chen, Wenzhe
Abstract: As one of the stimulators on bone formation, osteogenic growth peptide (OGP) improves both proliferation and differentiation of the bone cells in vitro and in vivo . The aim of this work was the preparation of three dimensional porous poly(ε-caprolactone) (PCL) scaffold with high porosity, well interpore connectivity, and then its surface was modified by using chitosan (CS)/OGP coating for application in bone regeneration. In present study, the properties of porous PCL and CS/OGP coated PCL scaffold, including the microstructure, water absorption, porosity, hydrophilicity, mechanical properties, and biocompatibility in vitro were investigated. Results showed that the PCL and CS/OGP-PCL scaffold with an interconnected network structure have a porosity of more than 91.5, 80.8%, respectively. The CS/OGP-PCL scaffold exhibited better hydrophilicity and mechanical properties than that of uncoated PCL scaffold. Moreover, the results of cell culture test showed that CS/OGP coating could stimulate the proliferation and growth of osteoblast cells on CS/OGP-PCL scaffold. These finding suggested that the surface modification could be a effective method on enhancing cell adhesion to synthetic polymer-based scaffolds in tissue engineering application and the developed porous CS/OGP-PCL scaffold should be considered as alternative biomaterials for bone regeneration.